CompTIA A+ complete video course library (220-901 + 220-902) : LiveLessons (LiveLessons (Indianapolis, Ind.), 2016)
"CompTIA A+ 220-901 and 220-902 Complete Video Course Library is a unique video product that provides complete coverage of all CompTIA A+ objectives so you can study for and pass the exams. The training provided in this library edition, which includes the CompTIA A+ 220-901 and CompTIA 220-902 Complete Video Courses, provides targeted and concise hands-on training that walks you through a learning path to successfully understand and absorb all key exam concepts. The modules in this course cover every objective in the CompTIA A+ 220-901 and 220-902 exams and can be used as your sole resource for learning the material needed to study for and pass both A+ exams. You can also use this as a supplement to other A+ training."--Resource description page